ASRO (Amphibious Spy Robot): Prototipe Robot Amfibi Pengintai dengan First Person View dan Sistem Navigasi berbasis Sensor Kompas - Rajif, R. Amirur; Arifin, Fatchul (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
Robots have an important role in all aspects of life, including the military field. The purpose of making this final project are building hardware and software of robot and to know the performance of robots. The method used in making the final project consists of identifying and analyzing requirements, designing and manufacturing hardware and software, and testing. The result of the performance of ASRO is that, the buoyancy force of the robot is greater than the weight of the object, namely Fa = 22,808 N and W = 15,696 N or Fa> W which makes the robot float while operate in the water field. The maximum range of control system robot is as far as 0-30 meters without obstacles and 0-15 meters with obstacles, while the monitoring system is as far as 0-75 meters without obstacles and 0-30 meters with obstacles. The Robot navigation system has a percentage of accuracy of reading 93.3% and the percentage response of the average robot when rotating 90â° is 100%, rotating 180â° is 100%, and rotating 270â° is 100%.